2004
DOI: 10.1097/01.psy.0000145821.25453.f7
|View full text |Cite
|
Sign up to set email alerts
|

Microarousals During Sleep Are Associated With Increased Levels of Lipids, Cortisol, and Blood Pressure

Abstract: Consistent with sleep restriction experiments, sleep fragmentation was associated with elevated levels of metabolic and cardiovascular risk indicators of stress-related disorders. Number of arousals also seems to be related to workload/stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
156
2
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 192 publications
(167 citation statements)
references
References 57 publications
6
156
2
3
Order By: Relevance
“…However, the interaction effect from the three-way ANOVA and the trend towards an interaction effect in the analysis of the morning values suggest that the overtime week was associated with an increase in the morning value at the end of the week, on Thursday. This finding may indicate that working overtime induced higher arousal, and this finding is supported by previous research that has found an association between high arousal and high morning cortisol (32). However, since the effect is rather weak, these data should be interpreted with caution.…”
Section: Tvaluesupporting
confidence: 75%
“…However, the interaction effect from the three-way ANOVA and the trend towards an interaction effect in the analysis of the morning values suggest that the overtime week was associated with an increase in the morning value at the end of the week, on Thursday. This finding may indicate that working overtime induced higher arousal, and this finding is supported by previous research that has found an association between high arousal and high morning cortisol (32). However, since the effect is rather weak, these data should be interpreted with caution.…”
Section: Tvaluesupporting
confidence: 75%
“…Glucose tolerance is also increased in sleep disorders (107), as are the levels of proinflammatory cytokines (108,109). In the study of young burnout participants mentioned earlier, the frequency of micro-arousals was significantly related to cortisol levels, systolic blood pressure, heart rate, and low-density lipoproteins (110).…”
Section: Stress and Sleep Physiologymentioning
confidence: 99%
“…Experimental and epidemiological studies that describe the effect of sleep deprivation on glucose metabolism and other physiologic parameters, focus on short sleep duration, regardless of the continuity or discontinuity of sleep. Whereas most research on sleep fragmentation investigates behavioral or cognitive consequences such as daytime sleepiness, vigilance and cognitive and psychomotor performance, Ekstedt et al 19 reported that sleep fragmentation was also associated with elevated cortisol and cholesterol levels. The role of sleep fragmentation in the relationship between sleep duration and obesity has, to our knowledge, not been described earlier.…”
Section: Introductionmentioning
confidence: 99%